Investigating Students’ Perspectives on the Role of Arabic as AaFoundation for Understanding Islamic Religious Education in the Digital Era - Attruk, Muhammad Fariq Heemal; Satriadi, Budi (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2026)
Purpose of the study: This study aims to explore students’ perspectives on the importance of Arabic as a foundation for understanding Islamic Religious Education in the digital era, focusing on how Arabic supports students’ comprehension of Islamic texts, learning experiences, and engagement with Islamic Religious Education content. Methodology: This study employed a qualitative case study approach. Data were collected through written open-ended interviews administered via Google Forms to 17 students from three study programs at an Islamic higher education institution. The data were analyzed using thematic analysis following Braun and Clarke’s framework. Main Findings: The findings indicate that students perceive Arabic as a fundamental foundation for understanding Islamic Religious Education, particularly in comprehending Qur’anic verses, religious terminology, and course materials. Arabic is viewed as a functional tool rather than the ultimate learning goal. Digital technology is utilized to support Arabic learning, especially for vocabulary and terminology, although it does not replace lecturers’ guidance. Students also face linguistic challenges, such as difficulties in nahwu (syntax), sarf (morphology), and limited vocabulary, as well as non-linguistic challenges related to motivation and the learning environment. Novelty/Originality of this study: While previous studies have predominantly examined the urgency of Arabic mastery, its curricular effectiveness, or the technical integration of digital media in Arabic and Islamic Religious Education learning, limited attention has been given to how students themselves interpret and negotiate Arabic as an epistemic foundation within digitally mediated learning environments. This study advances the literature by synthesizing students’ perspectives across four interrelated dimensions epistemic positioning, interpretive mediation, digitally mediated engagement, and multidimensional challenges thereby offering a more complex and experiential account of Arabic learning in Islamic higher education.